Evaluasi Pemanfaatan Aplikasi Pelaporan Orang Asing (APOA) Menggunakan Model Kesuksesan DeLone and McLean dan Importance Performance Analysis (IPA) (Studi Kasus : Kantor Imigrasi Kelas I Kota Malang) - Karimah Siti Wahyuni; Mochamad Chandra Saputra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Foreigner monitoring application (APOA) is an information system that is implemented by the Immigration government agency to facilitate the reporting process of foreigners to immigration. The problem that arises in the implementation of APOA at the Immigration Office in Malang is that the availability of hardware with old specifications makes APOA operations often disrupted, there are still some residences or companies that have not registered or reported the status of the Foreign Citizens in the community so that the foreigners' data entered at APOA is not 100% accurate. Evaluation of the utilization of the APOA information system was carried out using DeLone and McLean's success model and Importance Performance Analysis (IPA). The IPA was conducted by finding the value of the level of suitability and gap analysis before then be mapped using a Cartesian diagram to find the priority of improvement which is based on the 5 success variables of DeLone and McLean namely Quality System, Information Quality, Service Quality, User Satisfaction, and Net Benefits. The results of the evaluation show that the best performing variable is on the information quality with the level value of 100.6% and the positive gap (+) of 0.02. Recommendations are given to 10 indicators in 5 DeLone and McLean variables: Easy to Use, System Accuracy, Timeliness, Relevance, Usability, Assurance, Empathy, Adequacy, Effectiveness, and Productivity.